Crab shell-derived nitrogen-doped micro-/mesoporous carbon as an effective separator coating for high energy lithium–sulfur batteries. Issue 37 (12th September 2017) - Shao, Hongyuan; Ai, Fei; Wang, Weikun; Zhang, Hao; Wang, Anbang; Feng, Wang; Huang, Yaqin
Abstract : The synthesis of N-MIMEC from crab shell and the LiPS-trapping mechanisms of the N-MIMEC-coated separator during the discharge/charge process are demonstrated. Abstract : Lithium–sulfur (Li–S) batteries with high energy density are considered as promising for rechargeable energy storage. However, the shuttle effect hinders their practical application. Here, novel nitrogen-doped micro-/mesoporous carbon (N-MIMEC), derived from crab shells, was fabricated via a sustainable and cost-effective route. A modified separator coated with an N-MIMEC layer for Li–S batteries exhibits many advantages: (1) the micro-/mesopores provide enough surface area for sulfide adsorption, and accommodate the volume change; (2) the nitrogen in N-MIMEC enhances polysulfide adsorption and increases the electronic conductivity of the carbon framework; and (3) the conductive layer acts as an upper current collector, increasing the electrical conductivity. An enhanced Li–S battery with an N-MIMEC-coated separator was constructed, with an initial capacity of 1301 mA h g −1 and a high reversible capacity of 971.3 mA h g −1 after 100 cycles at 0.1C. Also, upon further increasing the sulfur loading from 63 wt% to 77 wt%, the corresponding Li–S batteries exhibit a high reversible capacity of 578 mA h g −1 after 500 cycles at 1C, with a decay rate of about 0.029% per cycle. Considering the green and sustainable source material, simple preparation and good electrochemical performance, the N-MIMEC-coated separator is promising for Li–S battery applications.